IMPLEMENTASI PEMBELAJARAN KONTEKSTUAL MODEL REACT PADA MATERI FLUIDA DINAMIS UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA SMA KELAS XI - Pati, Hasna; ', Zulirfan; ', Fakhruddin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research aimed to find out the improvement of the students motivation learning physic by applying REACT model of Contextual learning.This pre-experimental research used one group pretest and posttest design. There were 35 students of clas XI IPA I SMA Negeri 7 Pekanbaru have participated in this research. We used modification ARCS question one of motivation as instrument in collecting data, before and after treatment. The data were analyzed descriptive by using N-Gain. From the data, we found that N-Gain score in high category for all indicators. And, we can conclude that REACT model have improved students motivation in learning physis especially for class XI IPA I students of SMA Negeri 7 Pekanbaru.Key Words: ARCS, Learning Physics, REACT model